Negative Effects of a Multimodal Inpatient CBASP Program: Rate of Occurrence and Their Impact on Treatment Outcome in Chronic and Treatment-Resistant Depression - Herzog, Philipp; Häusler, Sophia; Normann, Claus; Brakemeier, Eva-Lotta (Frontiers in Psychiatry, 2021)
Background: A growing number of studies indicate that the Cognitive Behavioral Analysis System of Psychotherapy (CBASP) is effective in treating chronic depression. However, there is no systematic research into possible negative effects. Therefore, the objectives of the study were to investigate the rate of occurrence of negative effects of an inpatient CBASP program and their impact on treatment response. Methods: Patients with chronic depression and treatment resistance who completed the 12-week multimodal inpatient CBASP treatment program in an open trial (N = 52) retrospectively completed the Inventory for the Assessment of Negative Effects of Psychotherapy (INEP) during follow-up data collection. Severity of depressive symptoms was assessed self- and observer-rated at admission, discharge, and 6 months follow-up. Rates of occurrence of negative effects were calculated and binary logistic regression analyses were conducted to determine the relationship to treatment outcome. Results: The results indicate that 92.3% of patients reported having experienced at least one negative effect and 45.2% indicated dependence on their therapist. Stigmatization and financial concerns as well as intrapersonal changes were reported by about one-third. Only dependence on the therapist negatively impacted treatment outcome in both outcome measures. Conclusions: While almost all patients reported at least one negative effect of a multimodal inpatient CBASP treatment program, most of the reported negative effects appear to be benign. However, dependence on the therapist seems to have a negative impact on treatment outcome. If these results can be replicated in future large-scale, randomized controlled prospective studies, CBASP therapists should be aware of possible dependence and consciously address it during treatment.